Narasi Industri Pemasaran dan Konsumen Baru: Komunikasi Pemasaran Di Media Sosial dan Perilaku Pencarian Informasi Kalangan Milenial dan Centenial - Anindita Lintang Sari (PERSPEKTIF, 2022)
This article aims to explain social media marketing communication preference and information seeking behavior among digital natives, namely the Millennial and Centennial generations. By conducting a literature review on brand marketing communication on social media and information seeking behavior of millennial and centennial generations, there are both similarities and differences between the two generations preference. Similarities between the two generation lies in the use of social media as a source information about some brands. This causes both millennials and centennials prefer to contents that uploaded by other consumers on social media, both in attractive text and video formats. However, for the millennial generation, the use of influencers and word of mouth spread through social media content about a brand or product is said to have a greater impact than when messages about the brand are uploaded directly by the brand itself. Meanwhile, for the centennial generation, infomercial video format content is preferred and considered attractive compared to other marketing communication formats. In addition, for centennials, content by micro-influencers is also considered more trustworthy when compared to well-known influencers who are prefer by millenials. Therefore, it can be concluded that the difference in social media marketing communication preference for millennial and centennial generations lies on the uploader of the content and the format of the content itself.